Binge Drinking and Occupation, North Dakota, 2004-2005 - Dwayne W. Jarman, DVM, MPH; Timothy S. Naimi, MD, MPH; Stephen P. Pickard, MD; Walter Randolph Daley, DVM, MPH; Anindya K. De, PhD (Centers for Disease Control and Prevention, 2007)
IntroductionBinge drinking is a leading cause of preventable death and results in employee absenteeism and lost productivity. Knowledge about the prevalence of binge drinking among employees of different occupations is limited.MethodsWe assessed the prevalence of binge drinking (i.e., consuming five or more drinks per occasion during the previous 30 days) by primary occupation using data from the 2004-2005 North Dakota Behavioral Risk Factor Surveillance System. We used logistic regression to assess the association between binge drinking and primary occupation.ResultsOverall, 24.1% (95% confidence interval [CI], 22.5-25.7) of North Dakota workers reported binge drinking. The prevalence was highest among farm or ranch employees (45.3%; 95% CI, 28.3-63.4), food or drink servers (33.4%; 95% CI, 23.9-44.4), and farm or ranch owners (32.5%; 95% CI, 26.3-39.4). The prevalence was lowest among health care workers (13.2%; 95% CI, 10.3-16.8). Compared with health care workers, the adjusted odds of binge drinking were highest among farm or ranch employees (adjusted odds ratio [AOR], 2.2; 95% CI, 0.9-5.5), food or drink servers (AOR, 2.1; 95% CI, 1.1-4.0), and farm or ranch owners (AOR, 1.7; 95% CI, 1.1-2.6). Health insurance coverage was lowest among employees in occupations with the highest prevalence of binge drinking.ConclusionWe found occupational differences in the prevalence of binge drinking among employees in North Dakota. Many occupational categories had a high prevalence of binge drinking. We recommend the implementation of both employer-sponsored and population-based interventions to reduce binge drinking among North Dakota workers, particularly because employees in occupations with the highest rates of binge drinking had the lowest rates of health insurance coverage.